Стриптиз Жар-птицы: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2008)
Экземпляры: аб. ЦБ (20200302) / Инвентарный номер: 8555 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 67 / ББК: 84(2Рос=Рус)6